Health-Promoting Properties of Eucommia ulmoides: A Review - Hussain, Tarique (Evid Based Complement Alternat Med, 2016)
Eucommia ulmoides (EU) (also known as “Du Zhong” in Chinese language) is a plant containing various kinds of chemical constituents such as lignans, iridoids, phenolics, steroids, flavonoids, and other compounds. These constituents of EU possess various medicinal properties and have been used in Chinese Traditional Medicine (TCM) as a folk drink and functional food for several thousand years. EU has several pharmacological properties such as antioxidant, anti-inflammatory, antiallergic, antimicrobial, anticancer, antiaging, cardioprotective, and neuroprotective properties. Hence, it has been widely used solely or in combination with other compounds to treat cardiovascular and cerebrovascular diseases, sexual dysfunction, cancer, metabolic syndrome, and neurological diseases. This review paper summarizes the various active ingredients contained in EU and their health-promoting properties, thus serving as a reference material for the application of EU.